Leveling Entrepreneurial Skills of Vocational Secondary School Students in Indonesia: Impact of Demographic Characteristics - Susantiningrum, Susantiningrum; Siswandari, Siswandari; Joyoatmojo, Soetarno; Mafruhah, Izza (International Journal for Research in Vocational Education and Training, 2023)
Context: This article aims to determine the entrepreneurial skills of Vocational Secondary School students after the implementation of a new curriculum that promotes entrepreneurship courses in Indonesia. The authors believe that after taking such courses, students will be able to generate entrepreneurial skills. This study also explores the effect of demographic characteristics on students' entrepreneurship skills level, especially with respect to gender, school, and family. Approach: This study used a quantitative approach, with data collected through a questionnaire with five variables, that is, leadership, reflective communication, risk-taking, creatively innovative, and future orientation. Data were collected from 463 students who had taken entrepreneurship subjects that were chosen randomly. Data were analyzed using linear regression. Findings: 52.22% of our respondents had a moderate score for entrepreneurial skills, this is not in accordance with the expected learning outcomes, there are students who have entrepreneurial skills at a high level. With respect to creative innovation, in particular, a majority (53.15%) had a low score and 4.1% had a very low score. Moreover, family had a significant and positive effect on all dependent variables (leadership scores, reflective communication scores, risk-taking scores, creatively innovative scores, future orientation scores, and overall entrepreneurial skills scores). School demographic characteristics had a significant positive effect on the value of future orientation. These results indicate that private schools tend to strengthen the level of reflective communicative scores. Conclusion: The entrepreneurial skills of most vocational students are middling. This indicates that entrepreneurship subjects at Vocational Secondary schools have not been able to achieve their expected learning outcomes or help students develop entrepreneurial skills at a high level. Thus, further research is needed to determine the causes behind the problem. Schools are expected to be able to establish harmonious relationships by involving families to support the improvement of an informal learning environment that supports the mastery of entrepreneurial skills of vocational students.